Negative electrode active material, method for manufacturing negative electrode active material, negative electrode composition, negative electrode for lithium secondary battery comprising same, and lithium secondary battery comprising negative electrode
Patent Information
- Application Number
- CN202580021104.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-10-20
- Filing Date
- 2025-10-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0016]在根据本公开内容的一个实施方式的锂二次电池用负极活性材料的情况下,所述负极活性材料包含硅碳复合物,所述硅碳复合物包含沉积在多孔碳上的硅。在根据本公开内容的一个实施方式的硅碳复合物的情况下,在沉积过程期间,硅致密地沉积到所述多孔碳上,从而产生均匀的表面。
Smart Images

Figure CN123023141A_ABST
Abstract
Description
Technical Field
[0001] This application is based on and claims priority to Korean Patent Application No. 10-2024-0144998 filed on October 22, 2024, and Korean Patent Application No. 10-2025-0151521 filed on October 20, 2025, the disclosures of which are incorporated herein by reference in their entirety.
[0002] This disclosure relates to negative electrode active materials, methods for preparing negative electrode active materials, negative electrode compositions, negative electrodes for lithium secondary batteries containing the same, and lithium secondary batteries containing said negative electrodes. Background Technology
[0003] Due to the rapid increase in the use of fossil fuels, the demand for alternative or clean energy is growing, and one of the most active research areas is the generation and storage of electricity using electrochemical reactions.
[0004] A representative example of an electrochemical device that utilizes this electrochemical energy is the secondary battery, which is finding increasing applications.
[0005] On the other hand, with the development and increasing demand for mobile device technology, the demand for secondary batteries as an energy source is rapidly increasing. Among secondary batteries, lithium secondary batteries, which have high energy density and voltage, relatively long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, as electrodes for these high-capacity lithium secondary batteries, methods for manufacturing high-density electrodes with even higher energy density per unit volume are being actively researched. Summary of the Invention
[0006] Technical issues
[0007] In this disclosure, during the process of manufacturing silicon-carbon composites, the physical properties and composition of the porous carbon are adjusted and the deposition conditions are changed during the deposition of SiH4 onto porous carbon to improve the compactness of the internal pores of the silicon and control its resistance to plastic deformation. As a result, silicon-carbon composites manufactured under these conditions exhibit improved properties, such as reduced plastic deformation even when subjected to external pressure.
[0008] Therefore, this disclosure relates to negative electrode active materials according to the above-described technology, methods for preparing negative electrode active materials, negative electrode compositions, negative electrodes for lithium secondary batteries containing the above-described negative electrodes, and lithium secondary batteries containing said negative electrodes.
[0009] Technical means
[0010] One embodiment of this disclosure provides a negative electrode active material for lithium secondary batteries, the negative electrode active material for lithium secondary batteries comprising a silicon-carbon composite having a modulus value (A) of 15 GPa to 25 GPa and a hardness value (B) of 2,500 MPa to 5,000 MPa.
[0011] Another embodiment of this disclosure provides a method for manufacturing a negative electrode active material for lithium secondary batteries, the method comprising: preparing porous carbon; and depositing silicon onto the porous carbon to form a silicon-carbon composite, wherein, in the step of forming the silicon-carbon composite by depositing silicon onto the porous carbon, the amount of silicon is 40 parts by weight or more and 60 parts by weight or less based on 100 parts by weight of the silicon-carbon composite, the modulus value (A) of the silicon-carbon composite is 15 GPa to 25 GPa, and the hardness value (B) of the silicon-carbon composite is 2,500 MPa to 5,000 MPa.
[0012] Another embodiment of this disclosure provides a negative electrode composition for a lithium secondary battery, the negative electrode composition comprising a negative electrode active material according to this disclosure; a negative electrode conductive material; and a negative electrode binder.
[0013] Another embodiment of this disclosure provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and a negative electrode active material layer disposed on one or both sides of the negative electrode current collector layer, wherein the negative electrode active material layer comprises a negative electrode composition according to this disclosure or a cured thereof.
[0014] Another embodiment of this disclosure provides a lithium secondary battery comprising a positive electrode, a negative electrode for a lithium secondary battery according to this disclosure, a separator inserted between the positive electrode and the negative electrode, and an electrolyte.
[0015] Technical effect
[0016] In one embodiment of the negative electrode active material for a lithium secondary battery according to the present disclosure, the negative electrode active material comprises a silicon-carbon composite, the silicon-carbon composite comprising silicon deposited on porous carbon. In the case of the silicon-carbon composite according to one embodiment of the present disclosure, during the deposition process, silicon is densely deposited onto the porous carbon, thereby producing a uniform surface.
[0017] The negative electrode for the lithium secondary battery undergoes a process during manufacturing in which a negative electrode slurry is applied to the negative electrode current collector layer and then rolled. During this process, the composite negative electrode active material may crack due to the rolling pressure, resulting in silicon being exposed on the surface.
[0018] In the case of the silicon-carbon composite according to this disclosure, more uniform and dense silicon deposition is achieved by controlling the physical properties of the porous carbon precursor and adjusting the silicon deposition amount. Silicon-carbon composites manufactured under these conditions exhibit improved particle strength, thereby enhancing the capacity characteristics and lifespan of the battery.
[0019] The negative electrode for lithium secondary batteries comprising the silicon-carbon composite according to this disclosure ensures excellent capacity characteristics while minimizing side reactions on the surface of the active material, thereby improving resistance and enhancing lifetime performance against volume expansion. Attached Figure Description
[0020] The accompanying drawings illustrate embodiments of this disclosure and, together with the detailed description of this disclosure that follows, serve to further understand the technical concept of this disclosure. Therefore, this disclosure should not be construed as limited to the content shown in these drawings.
[0021] Figure 1 This is a flowchart illustrating a process for manufacturing a silicon-carbon composite according to one embodiment of the present disclosure.
[0022] Figure 2 This is a diagram illustrating a method for measuring physical properties according to this disclosure using a nanoindenter (top).
[0023] Figure 3 This is a diagram illustrating the stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present disclosure.
[0024] Figure 4 This is a diagram illustrating the stacked structure of a lithium secondary battery according to one embodiment of the present disclosure.
[0025] In the various figures of the accompanying drawings, corresponding reference numerals indicate corresponding parts. The figures are presented for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of some elements in the figures may be enlarged relative to other elements to aid in understanding the various embodiments. Furthermore, common but well-known elements that are useful or necessary in commercially viable embodiments are generally not depicted in order to provide clearer illustration of the figures of these various embodiments. Detailed Implementation
[0026] Before describing the contents of this disclosure, let’s first define some terms.
[0027] In this specification, unless otherwise specifically described, when a part is said to "contain" a constituent element, this does not exclude other constituent elements, but may include other constituent elements.
[0028] As used in this article, "p to q" refers to the range "above p and below q".
[0029] As used herein, "specific surface area" is measured by the Brunauer-Emmett-Teller (BET) method and is calculated using, for example, the BELSORP-mini II manufactured by BEL Japan Co., Ltd., from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K). For example, in this disclosure, BET specific surface area may refer to the specific surface area measured by the above-described measurement method.
[0030] As used herein, “Dn” denotes particle size distribution and refers to the particle size at the n% point of the cumulative particle number distribution according to particle size. For example, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution according to particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution according to particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution according to particle size. On the other hand, the average particle size can be measured using laser diffraction. For example, the powder to be tested is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in diffraction pattern according to particle size as the particles pass through the laser beam, thereby calculating the particle size distribution.
[0031] In one embodiment of this disclosure, particle size or particle diameter may refer to the average or representative diameter of each particle forming the metal powder.
[0032] As used herein, when a polymer contains a monomer as a monomeric unit, it means that the monomer participates in the polymerization reaction and is included in the polymer as a repeating unit. In this specification, when a polymer is described as containing a monomer, it is interpreted in the same way as saying that the polymer contains a monomer as a monomeric unit.
[0033] As used herein, unless specified as “homogeneous polymer,” the term “polymer” should be understood to be used broadly, including copolymers.
[0034] As used herein, weight-average molecular weight (Mw) and number-average molecular weight (Mn) are converted molecular weights of polystyrene measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) of various degrees of polymerization as standard materials for molecular weight measurement. In this specification, unless otherwise stated, molecular weight refers to weight-average molecular weight.
[0035] As used herein, the terms “about,” “approximately,” and “substantially” refer to a range or approximation of a value or degree that takes into account inherent manufacturing and material tolerances (e.g., ±5%).
[0036] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode comprises a negative electrode active material that intercalates and releases lithium ions from the positive electrode, and a silicon-based active material with high discharge capacity can be used as the negative electrode active material.
[0037] Recently, with the increasing demand for high-density energy batteries, there is a growing interest in using materials such as Si / C or SiO, which have a capacity approximately 10 times greater than that of graphite-based materials. x Methods for increasing capacity by using silicon compounds as the negative electrode active material are being studied. However, while silicon compounds, as high-capacity materials, have a large capacity compared to conventionally used graphite, a problem exists where they rapidly expand in volume during charging, which disrupts the conductive path and degrades battery characteristics.
[0038] To address these issues when using silicon-based compounds as anode active materials, various methods are being investigated, such as controlling the operating potential, coating the surface of the active material layer with a thin film, controlling the particle size of the silicon-based compound to suppress volume expansion, or preventing the conduction path from being broken. However, these methods have limitations in their application because they may actually reduce battery performance, and the commercialization of anode batteries with high silicon-based compound content remains a challenge.
[0039] In recent years, silicon-carbon composites in silicon-based active materials have been studied to ensure characteristics such as high energy density and fast charging. In the fabrication of the anode, a slurry containing the anode active material is applied to the anode current collector layer, followed by calendering. However, in the case of silicon-carbon composites, since silicon and carbon exist in a composite state, the composite is prone to cracking during the calendering process, thereby exposing the moisture-sensitive silicon to moisture. As a result, a problem of deteriorated lifetime characteristics arises.
[0040] In view of these problems, this disclosure provides a technique that can prevent or suppress damage to the conductive path due to the volume expansion of the silicon-carbon composite, even when the silicon-carbon composite is used as the negative electrode active material.
[0041] In the following description, embodiments of the present disclosure are illustrated with reference to the accompanying drawings to enable those skilled in the art to readily practice the present disclosure. However, the present disclosure can be implemented in various different forms and is not limited to the following description.
[0042] Figure 1 This is a flowchart illustrating a process for manufacturing a silicon-carbon composite according to one embodiment of the present disclosure.
[0043] refer to Figure 1According to one embodiment of the present disclosure, the process for manufacturing a silicon-carbon (Si / C) composite includes (S10) a step of carbonizing a resin-based raw material by heat treatment under appropriate conditions; (S20) a step of pulverizing and classifying the powder obtained by the carbonization step; (S30) a step of forming and enlarging pores by oxidizing the pulverized and classified carbon; and (S40) a step of depositing silicon onto the porous carbon that has formed pores.
[0044] On the other hand, the silicon-carbon composite prepared by the above steps is used to manufacture a negative electrode active material for lithium secondary batteries, and a negative electrode is manufactured by forming a negative electrode active material layer on a negative electrode current collector using the negative electrode active material.
[0045] On the other hand, for silicon-carbon composites manufactured through the above-described processes, their physical properties are evaluated by measuring the material's modulus and hardness. The modulus represents the material's stiffness, indicating its resistance to deformation under external forces, while the hardness represents the material's surface resistance to external scratches or indentations. For example, the modulus refers to the overall resistance to deformation of the material, while the hardness refers to the material's surface resistance to scratches or indentations.
[0046] refer to Figure 2 According to one embodiment of this disclosure, the modulus and hardness values can be measured by preparing an epoxy mold 7 containing the silicon-carbon composite and using a nanoindenter 3. The nanoindenter 3 is a device for measuring mechanical properties of materials, such as hardness, elastic modulus, and viscoelasticity, by applying minute forces to the material using a nanoscale indenter 5 and measuring the resulting changes in load and depth. The preparation of the epoxy mold 7 is described in more detail below.
[0047] One embodiment of this disclosure provides a negative electrode active material comprising a silicon-carbon composite having a modulus value (A) of about 15 GPa to about 25 GPa and a hardness value (B) of about 2,500 MPa to about 5,000 MPa.
[0048] Compared to using only carbon-based active materials, this disclosure improves capacity characteristics and achieves high energy density by including silicon-carbon composites as negative electrode active materials, and also enhances fast charging performance.
[0049] In this disclosure, the silicon-carbon composite refers to a composite of Si and C, which is distinct from silicon carbide (SiC).
[0050] In this disclosure, the silicon-carbon composite may include, but is not limited to, any conventionally manufactured silicon-carbon composite. For example, the composite may include a deposited or pulverized silicon-carbon composite.
[0051] In this disclosure, the silicon-based active material may be a silicon-carbon composite comprising porous carbon and silicon deposited on the porous carbon.
[0052] The silicon-carbon composite can be formed by combining silicon and graphite, and can form a structure in which the core of the silicon-graphite composite is surrounded by graphene or amorphous carbon. In the silicon-carbon composite, the silicon can be nano-silicon. For example, the nano-silicon can be silicon with a size in the range of about 1 nm to 999 nm.
[0053] In this disclosure, in order to improve the measurement accuracy of the modulus of silicon-carbon composites in powder form, epoxy resin can be used to prepare molded specimens for measurement.
[0054] For example, epoxy resin and epoxy curing agent are mixed in a 1:1 ratio, placed in a mold, and cured for 24 hours to form a first layer. Subsequently, the epoxy resin and epoxy curing agent are mixed again in a 1:1 ratio, and 1g of the silicon-carbon composite is added and mixed thoroughly. The mixture is then poured onto the first layer and cured to prepare an epoxy mold sample. After polishing the surface of the mold, 1g of the silicon-carbon composite to be tested is sampled, and the modulus is measured from the cross-section along the depth direction using a nanoindenter.
[0055] In this disclosure, the hardness value can be expressed as indentation hardness. Similar to the modulus, the hardness can be measured as follows: An epoxy mold sample is prepared, 1g of the silicon-carbon composite to be tested is taken, and the indentation hardness is measured along the depth direction from the cross-section using a nanoindenter. In this case, the indentation hardness (hardness) can be measured according to Equation 1-A: [Equation 1-A] Hardness = Pmax / A In Equation 1-A, “Pmax” represents the maximum load, and “A” represents the projected contact area.
[0056] When particles are indented using a nanoindenter, the material surface does not make perfect contact with the indenter, with some areas remaining uncontacted. Therefore, a difference arises between the total penetration depth and the actual contact depth. The hardness value can be derived from a correction value that compensates for this difference.
[0057] In one embodiment of this disclosure, the modulus value (A) of the silicon-carbon composite may be from about 15 GPa to about 25 GPa.
[0058] In another embodiment, the modulus value (A) of the silicon-carbon composite may be from about 15 GPa to about 25 GPa, for example from about 16 GPa to about 24 GPa, or from about 17 GPa to about 23 GPa.
[0059] In this disclosure, the hardness value (B) of the silicon-carbon composite may be from about 2,500 MPa to about 5,000 MPa, for example from about 3,000 MPa to about 4,900 MPa, or from about 3,500 MPa to about 4,700 MPa.
[0060] In this disclosure, the modulus value (A) and hardness value (B) of the silicon-carbon composite can satisfy Equation 1: [Formula 1] 0.1≤B 3 / A 2 In this disclosure, Equation 1 can be 0.1 ≤ B 3 / A 2 For example, 0.15≤B 3 / A 2 Or 0.16≤B 3 / A 2 And it can be B 3 / A 2 ≤0.45, B 3 / A 2 ≤0.44 or B 3 / A 2 ≤0.43.
[0061] In this disclosure, Formula 1 is used as an indicator of the degree of resistance of the silicon-carbon composite to particle fracture (e.g., plastic deformation) and to interpret analytical results in nanoindentation analysis.
[0062] Within this range, epoxy resin B alone 3 / A 2 The value is approximately 0.00046, while the B of the porous carbon used as a raw material for the silicon-carbon composite is... 3 / A 2 The values range from about 0.01 to about 0.03. The silicon-carbon composite with silicon deposited on the porous carbon exhibits larger values. By satisfying the range of Formula 1, the composite exhibits reduced plastic deformation of the negative electrode active material during slurry calendering, thereby providing the advantage of suppressing lifetime degradation and problems caused by silicon exposure.
[0063] In the silicon-carbon composite according to this disclosure, the modulus and hardness values fall within the aforementioned ranges and satisfy Equation 1, thereby producing suitable mechanical strength of the composite to prevent particle breakage during calendering. Furthermore, although excessive strength may hinder the formation of conductive pathways, the composite satisfying the scope of this disclosure also provides improved conductivity within the electrode.
[0064] In this disclosure, based on 100 parts by weight of the silicon-carbon composite, the silicon content in the silicon-carbon composite may be more than about 40 parts by weight and less than about 60 parts by weight, for example, more than about 43 parts by weight and less than about 60 parts by weight, or more than about 45 parts by weight and less than about 55 parts by weight.
[0065] When the amount of silicon deposited on the porous carbon meets the above range and the physical properties of the porous carbon are adjusted as described later, the above modulus and hardness values can be achieved, thereby improving capacity characteristics and also ensuring lifetime characteristics.
[0066] In this disclosure, the silicon-carbon composite further comprises a carbon coating. The composition and manufacturing method of the carbon coating may be those conventionally known in the art.
[0067] In this disclosure, the negative electrode active material may further include carbon-based active materials.
[0068] In this disclosure, the carbon-based active material may include graphite, and the graphite may include natural graphite and artificial graphite.
[0069] In this disclosure, the natural graphite may have an average particle size (D50) of about 5 μm to about 20 μm, and the artificial graphite may have an average particle size (D50) of about 5 μm to about 20 μm.
[0070] In another embodiment, the average particle size (D50) of the natural graphite may be from about 5 μm to 20 μm, for example from about 7 μm to 18 μm, or from about 9 μm to 15 μm.
[0071] In another embodiment, the average particle size (D50) of the artificial graphite may be from about 5 μm to 20 μm, for example from about 8 μm to 18 μm, or from about 10 μm to 16 μm.
[0072] In this disclosure, based on 100 parts by weight of the carbon-based active material, the weight ratio of artificial graphite to natural graphite can be from about 60:40 to 80:20.
[0073] In another embodiment, based on 100 parts by weight of the carbon-based active material, the weight ratio of artificial graphite to natural graphite may be about 60:40 to 80:20, for example about 65:35 to 78:22, or about 70:30 to 75:25.
[0074] In the case of graphite, both synthetic and natural graphite can be included. It has been confirmed that synthetic graphite exhibits superior single-cell characteristics compared to natural graphite, thus reducing the use of natural graphite and increasing the amount of synthetic graphite. However, from a cost perspective, synthetic graphite requires coking and graphitization processes, resulting in high processing costs. Therefore, when the above-mentioned range is met, both cost issues and improved cell characteristics can be addressed.
[0075] In this disclosure, based on 100 parts by weight of the negative electrode active material, the negative electrode active material may contain an amount of about 80 parts by weight or less of the silicon-carbon composite.
[0076] In another embodiment, based on 100 parts by weight of the negative electrode active material, the negative electrode active material may contain an amount of the silicon-carbon composite of about 80 parts by weight or less, for example, about 75 parts by weight or less, or about 70 parts by weight or less, about 1 part by weight or more, about 5 parts by weight or more, or about 10 parts by weight or more.
[0077] By ensuring the content of the negative electrode active material is within the aforementioned range, the capacity characteristics and energy density of the negative electrode can be guaranteed. For example, while increasing the content of the silicon-carbon composite can improve the energy density, it also leads to deterioration in cycle characteristics due to severe volume expansion. Conversely, reducing the content of the silicon-carbon composite makes it impossible to guarantee both high energy density and fast-charging performance. Therefore, using the aforementioned content allows for the achievement of both high energy density and improved fast-charging performance.
[0078] On the other hand, the average particle size (D50 particle size) of the silicon-carbon composite of this disclosure is about 1 μm and more but less than 10 μm, for example, about 2 μm to 8 μm, or it can be about 3 μm to 8 μm. When the average particle size is within the above range, the specific surface area of the particles is within an appropriate range, thereby forming a negative electrode slurry with a viscosity within an appropriate range. Therefore, the particles constituting the negative electrode slurry are dispersed smoothly. In addition, when the size of the silicon-carbon composite is greater than or equal to the lower limit range, since the negative electrode slurry is a composite made of conductive material and binder, the contact area between the silicon-carbon composite and the conductive material is excellent, which increases the possibility of the conductive network being sustained, thereby increasing the capacity retention rate. On the other hand, when the average particle size meets the above range, there are no excessively large silicon particles, which allows for the smooth formation of the negative electrode surface, thus suppressing the phenomenon of uneven current density during charging and discharging.
[0079] In one embodiment of this disclosure, the silicon-carbon composite typically has a characteristic BET specific surface area. According to one embodiment, the BET specific surface area of the silicon-carbon composite is approximately 0.01 m². 2 / g to 150m 2 / g, approximately 0.1m 2 / g to 100m 2 / g, approximately 0.2m 2 / g to 80m 2 / g, or approximately 0.2m 2 / g to 18m 2 / g. The BET specific surface area is measured (using nitrogen) according to DIN 66131.
[0080] In one embodiment of this disclosure, the silicon in the silicon-carbon composite may be present in a crystalline or amorphous form, and the silicon may be, for example, spherical or fragmented particles. Alternatively, the silicon may also have a fibrous structure, or may be present in the form of a silicon-containing film or coating.
[0081] In one embodiment of this disclosure, the silicon-carbon composite may have a non-spherical shape, and its sphericity (roundness) is, for example, less than about 0.9, about 0.7 to 0.9, about 0.8 to 0.9, or about 0.85 to 0.9.
[0082] In this disclosure, the sphericity is determined by the following formula 1-B, where A is the area and P is the boundary line.
[0083] [Equation 1-B]
[0084] 4πA / P 2
[0085] In one embodiment of this disclosure, a negative electrode composition for a lithium secondary battery is provided, the negative electrode composition for a lithium secondary battery comprising, as described above, a negative electrode active material, a negative electrode conductive material, and a negative electrode binder.
[0086] In one embodiment of this disclosure, a negative electrode composition is provided, wherein, based on 100 parts by weight of the negative electrode composition, the negative electrode active material is about 40 parts by weight or more.
[0087] In another embodiment, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode active material may be more than about 40 parts by weight, for example more than about 60 parts by weight, more than about 65 parts by weight, or more than about 70 parts by weight, and may be less than about 99 parts by weight, for example less than about 98 parts by weight, or less than about 96 parts by weight.
[0088] Even when the silicon-carbon composite with significantly high capacity within the above-mentioned range is used, the negative electrode composition according to this application, by using a negative electrode active material that satisfies a specific pore distribution and suppresses volume expansion and side reactions during charge and discharge, ensures that the performance of the negative electrode does not deteriorate even if the content is within the above-mentioned range, and that the output characteristics during charge and discharge are excellent.
[0089] Conventionally, graphite compounds are typically used as the negative electrode active material. However, with the increasing demand for high-capacity batteries, there has been a growing trend of experimenting with the mixing and use of silicon-based active materials to increase capacity. However, even when the properties of silicon-based active materials are adjusted as described above, there may be issues with rapid volume expansion during charge and discharge processes, which could damage the conductive pathways formed within the negative electrode active material layer.
[0090] Therefore, in one embodiment of this disclosure, the negative electrode conductive material may include at least one selected from dot-shaped conductive materials, sheet-shaped conductive materials, and linear conductive materials.
[0091] In one embodiment of this disclosure, the dot-shaped conductive material can be used to improve the conductivity of the negative electrode, and refers to a dot-shaped or spherical conductive material that has conductivity without causing chemical changes. For example, the dot-shaped conductive material may include at least one selected from: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, conductive fibers, fluorocarbons, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives. For example, carbon black may be included in relation to the ability to achieve high conductivity and excellent dispersibility.
[0092] In one embodiment of this disclosure, the dot-shaped conductive material may have a diameter of approximately 40 μm. 2 / g or more and 70m 2 / g or less, for example, about 45m 2 / g or more and 65m 2 / g or about 50m 2 / g or more and 60m 2 BET specific surface area below / g.
[0093] In one embodiment of this disclosure, the dot-shaped conductive material may have a functional group (volatile) content of about 0.01% and less than 1%, for example, about 0.01% and less than 0.3%, or about 0.01% and less than 0.1%.
[0094] When the functional group content of the dot-shaped conductive material meets the above-mentioned range, the functional groups exist on the surface of the dot-shaped conductive material, allowing the dot-shaped conductive material to be readily dispersed in the solvent when water is used as the solvent. In this disclosure, by using specific silicon-based active materials, the functional group content of the dot-shaped conductive material can be reduced, thereby achieving an excellent effect of improving dispersibility.
[0095] In one embodiment of this disclosure, the material comprises both a silicon-based active material and a dot-shaped conductive material having a functional group content within the aforementioned range, and the content of the functional groups can be controlled according to the degree of heat treatment of the dot-shaped conductive material.
[0096] In one embodiment of this disclosure, the particle size of the dot-like conductive material may be about 10 nm to 100 nm, for example about 20 nm to 90 nm, or about 20 nm to 60 nm.
[0097] In one embodiment of this disclosure, the conductive material may comprise a sheet-like conductive material.
[0098] The function of the sheet-like conductive material is to improve conductivity by increasing the surface contact between silicon particles in the negative electrode, while suppressing the breakage of the conductive path caused by volume expansion. The sheet-like conductive material can be represented as a plate-like conductive material or a bulk-like conductive material.
[0099] In one embodiment of this disclosure, the sheet-like conductive material may comprise at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and in one embodiment, the sheet-like conductive material may be plate-like graphite.
[0100] In one embodiment of this disclosure, the average particle size (D50) of the sheet-like conductive material can be about 2 μm to 7 μm, for example, about 3 μm to 6 μm, or about 3.5 μm to 5 μm. When the above ranges are met, the particle size is sufficient to promote dispersion without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersion is performed using the same equipment and time, the dispersion effect is excellent.
[0101] In one embodiment of this disclosure, the sheet-like conductive material may be a high specific surface area sheet-like conductive material with a high BET specific surface area; or a low specific surface area sheet-like conductive material.
[0102] In one embodiment of this disclosure, either a high specific surface area sheet-like conductive material or a low specific surface area sheet-like conductive material can be used as the sheet-like conductive material without any limitation. However, since the sheet-like conductive material according to this disclosure may affect electrode performance to some extent through dispersion, a low specific surface area sheet-like conductive material that will not cause dispersion problems can be used.
[0103] In one embodiment of this disclosure, the sheet-like conductive material may have a thickness of approximately 1m. 2 BET specific surface area above / g.
[0104] In another embodiment, the sheet-like conductive material may have a thickness of approximately 1m.2 / g or more and 500m 2 / g or less, for example, about 5m 2 / g or more and 300m 2 / g or about 5m 2 / g or more and 250m 2 BET specific surface area below / g.
[0105] The sheet-like conductive materials according to this disclosure can be either high specific surface area sheet-like conductive materials or low specific surface area sheet-like conductive materials.
[0106] In another embodiment, the sheet-like conductive material is a high specific surface area sheet-like conductive material, and can have a surface area of about 50 μm. 2 / g to 500m 2 / g, for example, about 80m 2 / g to 300m 2 / g, or approximately 100mg 2 / g to 300m 2 BET specific surface area within the range of / g.
[0107] In yet another embodiment, the sheet-like conductive material is a low specific surface area sheet-like conductive material, and can have a surface area of approximately 1m². 2 / g to 40m 2 / g, for example, about 5m 2 / g to 30m 2 / g, or approximately 5mg 2 / g to 25m 2 BET specific surface area within the range of / g.
[0108] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. A bundled carbon nanotube may comprise multiple carbon nanotube units. Here, unless otherwise stated, the term "bundled" refers to a secondary shape in the form of a bundle or rope, wherein multiple carbon nanotube units are arranged parallel or intertwined in a manner where the longitudinal axis orientation of the carbon nanotube units is substantially the same. The carbon nanotube units have cylindrical graphite sheets with nanometer-scale diameters and sp... 2 Bonded structure. At this point, depending on the curling angle and structure of the graphite sheet, it can exhibit conductor or semiconductor properties. Compared to wound carbon nanotubes, the bundled carbon nanotubes can be uniformly dispersed during the fabrication of the negative electrode and can smoothly form a conductive network within the negative electrode, thereby improving the conductivity of the negative electrode.
[0109] In this disclosure, a negative electrode composition is provided, wherein, based on 100 parts by weight of the negative electrode composition, the negative electrode conductive material is about 20 parts by weight or less.
[0110] In another embodiment, based on 100 parts by weight of the negative electrode composition, the negative electrode conductive material is about 20 parts by weight or less, about 17 parts by weight or less, or about 15 parts by weight or less, and is about 0.01 parts by weight or more or about 0.02 parts by weight or more.
[0111] The negative electrode conductive material according to this disclosure has a composition completely independent of the positive electrode conductive material used in the positive electrode. For example, the negative electrode conductive material according to this disclosure serves to maintain the contact points between silicon-based active materials that expand significantly in electrode volume due to charging and discharging, while the positive electrode conductive material serves to buffer during rolling and provide a certain degree of conductivity. Therefore, its composition and function are completely different from the negative electrode conductive material of this disclosure.
[0112] Furthermore, the negative electrode conductive material according to this disclosure is applied to silicon-based active materials and has a different composition than the conductive material applied to graphite-based active materials. For example, the conductive material used in an electrode with graphite-based active materials has only particles smaller than those of the active material, thus possessing properties that improve output characteristics and impart a certain degree of conductivity, and is completely different in composition and function from the negative electrode conductive material applied together with silicon-based active materials as described in this disclosure.
[0113] In one embodiment of this disclosure, the sheet-like conductive material used as the negative electrode active material has a different structure and function than the carbon-based active material typically used as the negative electrode active material. For example, the carbon-based active material used as the negative electrode active material can be artificial graphite or natural graphite, and refers to a material processed into spherical or dot-like forms to facilitate the storage and release of lithium ions.
[0114] On the other hand, the sheet-like conductive material used as the negative electrode conductive material is a material having a sheet or plate shape, and can be represented as plate-like graphite. For example, the sheet-like conductive material refers to a material contained in order to maintain a conductive path within the negative electrode active material layer, and refers to a material that ensures a sheet-like conductive path within the negative electrode active material layer, rather than a material that functions in storing and releasing lithium.
[0115] In this disclosure, using sheet-like graphite as a conductive material means processing it into sheet or sheet form and using it as a material to ensure a conductive path rather than to store or release lithium. In this case, the negative electrode active material included together has high capacity properties for lithium storage and release, and serves to store and release all lithium ions transferred from the positive electrode.
[0116] Furthermore, in this disclosure, using carbon-based active materials as active materials means processing them into dots or spheres and using them as materials for storing or releasing lithium.
[0117] In one embodiment of this disclosure, the artificial or natural graphite, as a carbon-based active material, can have a dot-like structure and satisfy approximately 0.1 μm. 2 / g or more and 4.5m 2 The BET specific surface area is in the range of less than / g. Furthermore, the plate-shaped graphite, as a sheet-like conductive material, can be in sheet form with a surface area of approximately 5m². 2 BET specific surface area above / g.
[0118] In one embodiment of this disclosure, the negative electrode adhesive may comprise at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by Li, Na, or Ca, and may also comprise various copolymers thereof.
[0119] According to one embodiment of this disclosure, a negative electrode adhesive is used to retain the active material and the conductive material to suppress and mitigate the distortion and structural deformation of the negative electrode structure during the volume expansion of the silicon-based active material, and any general adhesive can be applied when the above-mentioned effects are achieved. For example, a water-based adhesive or a PAM-based adhesive can be used.
[0120] In one embodiment of this disclosure, based on 100 parts by weight of the negative electrode composition, the negative electrode adhesive may be about 30 parts by weight or less, for example, about 25 parts by weight or less, or about 20 parts by weight or less, and may be about 5 parts by weight or more, or about 10 parts by weight or more.
[0121] In one embodiment of this disclosure, a method for manufacturing a negative electrode active material is provided, the method comprising: preparing porous carbon; and depositing silicon onto the porous carbon to form a silicon-carbon composite. In the step of forming the silicon-carbon composite by depositing silicon onto the porous carbon, based on 100 parts by weight of the silicon-carbon composite, the amount of silicon is more than about 40 parts by weight and less than about 60 parts by weight, the modulus value (A) of the silicon-carbon composite is from about 15 GPa to about 25 GPa, and the hardness value (B) of the silicon-carbon composite is from about 2,500 MPa to about 5,000 MPa.
[0122] In this disclosure, the porous carbon may have a first pore diameter of less than about 2 nm, as measured by nitrogen adsorption, a ratio of more than 90%, and a second pore diameter of more than about 2 nm to less than about 50 nm, as measured by nitrogen adsorption, a ratio of less than 10%.
[0123] This disclosure achieves the aforementioned physical properties by appropriately selecting the conditions for the porous carbon as described above. For example, in the manufacture of the silicon-carbon composite, when the micropore volume of the porous carbon is about 90% or more and porous carbon made of resin instead of biomass is used, the rigidity of the resulting silicon-carbon composite is enhanced. Therefore, the aforementioned physical properties are satisfied, thereby the composite exhibits characteristics that enhance the lifespan of secondary batteries.
[0124] In addition, this disclosure provides a method for manufacturing a negative electrode active material, wherein the sphericity defined by Formula 1 is about 0.7 to 0.9: [Formula 1] 4πA / P 2 In Equation 1, "A" is the area and "P" is the perimeter.
[0125] When the physical properties of the porous carbon are controlled as described above, mechanical rigidity is enhanced, and by using porous carbon that satisfies the physical properties, silicon density and deposition uniformity can be improved during deposition.
[0126] According to one embodiment, this disclosure provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and a negative electrode active material layer disposed on one or both sides of the negative electrode current collector layer, wherein the negative electrode active material layer comprises a negative electrode composition or a cured form thereof according to this disclosure.
[0127] Figure 3 This is a diagram illustrating the stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present disclosure.
[0128] refer to Figure 3 The negative electrode 100 for lithium secondary batteries contains a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10. Figure 3 The diagram shows that the negative electrode active material layer 20 is formed on one surface of the negative electrode current collector layer 10, but the negative electrode active material layer 20 may also be formed on both surfaces of the negative electrode current collector layer 10.
[0129] In one embodiment of this disclosure, the negative electrode 100 for a lithium secondary battery can be formed by applying a negative electrode slurry containing the negative electrode composition to one or both sides of the negative electrode current collector layer 10 and drying it.
[0130] At this time, the negative electrode slurry may contain a negative electrode composition and a slurry solvent.
[0131] In one embodiment of this disclosure, the solid content of the negative electrode slurry can be in the range of about 5% to 40%.
[0132] In another embodiment, the solid content of the negative electrode slurry may be in the range of about 5% to 40%, for example about 7% to 35%, or about 10% to 30%.
[0133] The solid content of the negative electrode slurry can refer to the content of the negative electrode composition contained in the negative electrode slurry, and can be expressed as the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0134] When the solid content of the negative electrode slurry is within the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, so as to minimize particle agglomeration of the negative electrode composition and enable the negative electrode active material layer to be formed efficiently.
[0135] In one embodiment of this disclosure, the slurry solvent can be used without limitation, as long as the slurry solvent is capable of dissolving the negative electrode composition, and examples may include water or NMP (N-methyl-2-pyrrolidone).
[0136] In one embodiment of this disclosure, the negative electrode current collector layer 10 typically has a thickness of about 1 μm to 100 μm. There are no particular limitations on the negative electrode current collector layer 10, as long as it has high conductivity without causing chemical changes in the battery, and examples include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel with a surface treated with carbon, nickel, titanium, or silver, and aluminum-cadmium alloys. Furthermore, the negative electrode current collector layer may have fine irregularities formed on its surface to enhance the bonding strength of the negative electrode active material, and can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0137] In one embodiment of this disclosure, a negative electrode 100 for a lithium secondary battery is provided, wherein the negative electrode current collector layer 10 has a thickness of about 1 μm or more to about 100 μm or less, and the negative electrode active material layer 20 has a thickness of about 5 μm or more to about 500 μm or less.
[0138] However, the thickness can be modified in various ways depending on the type and purpose of the negative electrode 100 used, and is not limited thereto.
[0139] In one embodiment of this disclosure, the porosity of the negative electrode active material layer 20 may be more than about 10% and less than 60%.
[0140] In another embodiment, the porosity of the negative electrode active material layer 20 may be more than about 10% and less than 60%, for example, more than about 20% and less than 50%, or more than about 25% and less than 45%.
[0141] The porosity varies depending on the composition and content of the silicon-based active material, the conductive material, and the binder contained in the negative electrode active material layer 20. By including the silicon-based active material and conductive material according to this disclosure in a specific composition and content, the above range is satisfied, and therefore, the conductivity and resistance of the electrode have an appropriate range.
[0142] In one embodiment of this disclosure, a lithium secondary battery is provided, the lithium secondary battery comprising a positive electrode, a negative electrode for a lithium secondary battery according to this disclosure, a separator inserted between the positive electrode and the negative electrode, and an electrolyte.
[0143] Figure 4 A stacked structure of a secondary battery 300 according to one embodiment of the present disclosure is shown. For example, the negative electrode 100 for the lithium secondary battery includes the negative active material layer 20 on one side of the negative current collector layer 10, and the positive electrode 200 for the lithium secondary battery includes the positive active material layer 40 on one side of the positive current collector layer 50. Furthermore, the negative electrode 100 and the positive electrode 200 for the lithium secondary battery, together with a separator 30 interposed therebetween, form a stacked structure.
[0144] According to one embodiment of this disclosure, a lithium secondary battery 300 may include a negative electrode 100 for a lithium secondary battery as described above. The lithium secondary battery 300 may include the negative electrode 100, a positive electrode 200, a separator 30 inserted between the positive electrode 200 and the negative electrode 100, and an electrolyte (not shown). The negative electrode 100 is the same as described above. Since the negative electrode 100 has already been described, further description is omitted.
[0145] The positive electrode 200 may include a positive electrode current collector 50 and a positive electrode active material layer 40 formed on the positive electrode current collector 50 and containing positive electrode active material.
[0146] In the positive electrode 200, there are no particular limitations on the positive electrode current collector 50, as long as it is conductive and will not cause chemical changes in the battery. Examples of such materials include stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum or stainless steel with a surface treated with carbon, nickel, titanium, or silver. The positive electrode current collector 50 can typically have a thickness of about 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode current collector 50 to enhance the bonding strength of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0147] The positive electrode active material can be a commonly used positive electrode active material. For example, the positive electrode active material can be a layered compound, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; lithium iron oxide, such as LiFe3O4; lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; and LiNi 1-c2 M c2 O2 (where M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≤c2≤0.3) represents Ni-site type lithium nickel oxide; LiMn 2-c3 M c3 Lithium-manganese composite oxides represented by O2 (where M is at least one selected from Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01 ≤ c3 ≤ 0.1) or Li2Mn3MO8 (where M is at least one selected from Fe, Co, Ni, Cu, and Zn); LiMn2O4, wherein a portion of the Li in the chemical formula is replaced by an alkaline earth metal ion; however, this disclosure is not limited thereto. The positive electrode may be Li metal.
[0148] The positive electrode active material layer 40 may include a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0149] The positive electrode conductive material used to impart conductivity to the electrode can be any conductive material that will not cause a chemical change in the constructed battery, without any particular limitation. Examples include graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fiber; metal powders or metal fibers, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, which can be used alone or in mixtures of two or more thereof.
[0150] The positive electrode adhesive is used to improve the adhesion between positive electrode active material particles and the adhesion strength between the positive electrode active material and the positive electrode current collector. Examples include polyvinylidene fluoride (PVDF), PVDF-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, which may be used alone or in mixtures of two or more thereof.
[0151] The separator 30 separates the negative electrode 100 from the positive electrode 200 and provides a migration channel for lithium ions. Any separator commonly used in secondary batteries can be used without particular limitation, and any material with low resistance to ion migration in the electrolyte and excellent electrolyte retention can be selected. For example, the separator 30 used can be a porous polymer membrane, such as a porous polymer membrane made of polyolefin polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof. Alternatively, conventional porous nonwoven fabrics, such as nonwoven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc., can be used as the separator 30. Furthermore, separators coated with ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and can be selectively used in single-layer or multi-layer structures.
[0152] The electrolytes used in this disclosure may include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to manufacture lithium secondary batteries 300.
[0153] The electrolyte may contain non-aqueous organic solvents and metal salts.
[0154] Examples of the non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0155] Among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, are high-viscosity organic solvents with high dielectric constants and exhibit effective dissociation capabilities for lithium salts. When these cyclic carbonates are mixed with low-viscosity, low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in appropriate ratios, electrolytes with high conductivity can be obtained.
[0156] The metal salt may be a lithium salt, and the lithium salt is a substance readily soluble in the non-aqueous electrolyte. For example, the anion of the lithium salt may be at least one selected from the following: F - Cl - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - .
[0157] In addition to the electrolyte components mentioned above, the electrolyte may further contain one or more additives, such as the following, for the purpose of improving battery life characteristics, suppressing battery capacity reduction, and improving battery discharge capacity: alkyl halides of carbonate such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoric triamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum trichloride.
[0158] One embodiment of this disclosure provides a battery module comprising the lithium secondary battery 300 as a unit cell and a battery pack comprising the battery module. Because the battery module and the battery pack comprise the secondary battery 300 having high capacity, high rate capability, and cycle performance, they can be used as a power source for medium to large-sized devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.
[0159] Methods of implementing the invention
[0160] In the following description, embodiments are provided to aid in understanding this disclosure; however, these embodiments are merely examples of this disclosure, and it will be apparent to those skilled in the art that various modifications and variations can be made within the spirit and scope of this disclosure. It should be understood that such modifications and variations fall within the scope of the appended claims.
[0161] <Preparation Example>
[0162] <Example 1>
[0163] The resin-based raw material is placed in a tube furnace, and the atmosphere inside the furnace is replaced with an inert gas by flowing argon at a rate of 50 ml / min to 200 ml / min for 2 hours without raising the temperature. Then, the temperature is increased to 400°C at a rate of 5°C / min, followed by heating in an argon atmosphere for 2 hours. Subsequently, the temperature is further increased to 900°C at a rate of 5°C / min, and a carbonization process is performed by heating in an argon atmosphere for 2 hours.
[0164] After the reaction, the resulting powder was washed with ethanol 2 to 3 times.
[0165] Carbon-based particles dried at 100°C for more than 12 hours were mixed with KOH at a weight ratio of 1:4 and heated at 700°C under an argon atmosphere for 4 hours to expand the pores. The mixture was then washed with distilled water and dried again at 100°C for more than 12 hours. The porous carbon obtained through this activation process exhibited a 97% proportion of first pores with a diameter less than 2 nm, and a pore size of 0.87 nm, as measured by nitrogen adsorption. 3 / g total pore volume and approximately 1,800m 2 / g to 2,000m 2 Specific surface area per g.
[0166] The porous carbon includes a spheroidization step during the manufacturing process, and the spheroidization can be carried out by a method selected from spray drying, rotary atomization, or a sol-gel process. Subsequently, a classification process is performed to remove fine particles smaller than 1 μm.
[0167] Graded porous carbon was placed in the hot zone of a CVD apparatus, and a SiH4 / H2 = 5 / 95 mixed gas was flowed at 600°C at a rate of 50 to 210 ml / min for 6 hours under low pressure conditions of approximately 1 to 10 Torr to produce a silicon-carbon composite. Without removing the sample from the furnace, the furnace temperature was increased to 650°C at a rate of 5°C / min while argon gas continued to flow. Then, a C2H2 / H2 / Ar = 10 / 50 / 40 mixed gas was flowed at 200 ml / min and reacted for 3 hours to form a carbon coating on the surface, thereby producing a silicon-carbon composite with a carbon layer on its surface.
[0168] <Example 2>
[0169] Except that the porous carbon has a lower sphericity due to the absence of a spheroidizing process, the silicon-carbon composite is manufactured in the same manner as in Example 1.
[0170] <Example 3>
[0171] Biomass-based raw materials such as cellulose powder and coconut shells are used instead of resin-based raw materials, and a physical activation method is used. In this physical activation method, carbon-based particles dried at 100°C for more than 12 hours are heated at 700°C for 3 hours in an argon atmosphere containing 10% to 20% CO2 as a balancing gas to expand the pores. Otherwise, the silicon-carbon composite is manufactured in the same manner as in Example 1.
[0172] <Comparative Example 1>
[0173] After carbonizing biomass raw materials, such as cellulose powder and coconut shells (not resin-based raw materials), which serve as precursors for porous carbon, by heat treatment at 500°C to 1000°C under an inert gas atmosphere, the carbonized porous carbon is pulverized and graded. Then, the porous carbon is physically activated by oxidizing it with an oxidizing gas (steam, CO2, O2, etc.) to form pores. The resulting porous carbon is non-spherical, with a first pore diameter less than 2 nm accounting for 92% and a second pore diameter greater than 2 nm accounting for 8% as measured by nitrogen adsorption, exhibiting a diameter of approximately 0.75 nm. 3 / g total pore volume and approximately 1,600m 2 Specific surface area per g.
[0174] Without performing a separate grading process to remove fine powder, porous carbon is placed in the hot zone of a CVD apparatus, and a gas mixture of SiH4 / H2 = 5 / 95 is flowed at a rate of 50 ml / min to 210 ml / min for 3 hours at 600°C and a low pressure of 1 to 10 Torr to produce a silicon-carbon composite.
[0175] Without removing the composite from the furnace, the furnace temperature is increased to 650°C at a rate of 5°C / min while only Ar gas is flowing through it. Then, a mixed gas of C2H2 / H2 / Ar = 10 / 50 / 40 is flowed at 200 ml / min for 1 hour to carry out the reaction and form a carbon layer on the surface of the silicon-carbon composite.
[0176] <Comparative Example 2>
[0177] In the activation process of the porous carbon, carbon-based particles dried at 100°C for more than 12 hours are heated at 700°C for 5 hours in an argon atmosphere containing 10% to 20% CO2 as the equilibrium gas to expand the pores. The porous carbon prepared by this method exhibits a pore size of approximately 1,800 μm. 2 Specific surface area per g.
[0178] The silicon-carbon composite was manufactured in the same manner as in Comparative Example 1, except that the processing time in the SiH4 CVD process was 5 hours and no carbon layer was formed on the surface.
[0179] <Comparative Example 3>
[0180] Except for the SiH4 CVD process, which has a processing time of 1 hour and the process of forming a carbon layer on the surface, which has a processing time of 7 hours, the silicon-carbon composite was manufactured in the same manner as in Comparative Example 1.
[0181] <Comparative Example 4>
[0182] Except that the SiH4 CVD process is performed for 1 hour and the process of forming a carbon layer on the surface is carried out at 580°C for 4 hours, the silicon-carbon composite is manufactured in the same manner as Comparative Example 1.
[0183] <Comparative Example 5>
[0184] In Example 2, carbon-based particles and KOH were mixed at a weight ratio of 1:5, the stirring time was increased by 30 minutes, and the mixture was heated at 700°C for 7 hours for activation. Afterward, the mixture was washed with distilled water and dried again at 100°C for at least 12 hours.
[0185] The porous carbon obtained through the activation process exhibits a 97% proportion of first pores with a diameter less than 2 nm, as measured by nitrogen adsorption, and a diameter of 1.1 nm. 3 / g total pore volume and approximately 2,000 m 2 / g to 2,200m 2 Specific surface area per g.
[0186] The silicon-carbon composite was manufactured in the same manner as in Example 2, except that the silicon deposition process was carried out for 5 hours and no carbon layer was formed on the surface.
[0187] <Comparative Example 6>
[0188] Except that the carbon-based particles and KOH were mixed at a weight ratio of 1:3, porous carbon was prepared in the same manner as in Example 1, and the porous carbon thus prepared had a density of 0.75 μm. 3 The total pore volume per g is between 1,600 and 1,800 m³. 2 Specific surface area within the range of / g.
[0189] Graded porous carbon was placed in the hot zone of a CVD apparatus, and a SiH4 / H2 = 5 / 95 mixed gas was flowed at 600°C at a rate of 50 to 210 ml / min for 4 hours under low pressure conditions of approximately 1 to 10 Torr to produce a silicon-carbon composite. Without removing the sample from the furnace, the furnace temperature was increased to 650°C at a rate of 5°C / min while argon gas continued to flow. The manufacturing procedure was the same as in Example 1, except that a C2H2 / H2 / Ar = 10 / 50 / 40 mixed gas was flowed at 200 ml / min for 7 hours to allow the reaction and form a carbon layer on the surface.
[0190] <Comparative Example 7>
[0191] (1) Preparation of magnesium-containing silicon oxides
[0192] In crucible 1, Si and SiO2 are mixed in a 1:1 molar ratio and heated to a sublimation temperature of 1,400 °C. In crucible 2, metallic magnesium is heated separately and evaporated at a temperature between 600 °C and 1,000 °C.
[0193] Both crucibles were kept under a reduced pressure of approximately 0.1 Torr. The Mg-containing vapor mixture obtained from crucibles 1 and 2 was reacted for 6 hours, and then condensed into a solid phase at 800 °C in a vacuum region.
[0194] The silicon-based active material prepared by the above method was pulverized using a ball mill for approximately 3 to 4 hours to produce particles with a D50 of approximately 6 μm. Subsequently, methane (CH4) was milled at 10 μm under an inert Ar atmosphere. -1 The material was introduced into a CVD apparatus at a pressure of 1 L / min for approximately 5 hours to form a carbon layer on the surface of the silicon-based active material, thereby producing magnesium-containing silicon oxide. The Mg content in the powder was determined to be 8% by weight by ICP-MS analysis.
[0195] For the active materials prepared in the examples and comparative examples, the modulus and hardness values were measured, and the results are shown in Table 1 below.
[0196] [Table 1]
[0197] For reference, Example 1 used resin-based spherical porous carbon, and Example 2 showed a value of 0.2008 in Formula 1, which is lower than the value of Example 1 (0.21576) because Example 2 did not undergo a spheroidizing process. Furthermore, since Example 3 used biomass-derived raw materials, the porous carbon exhibited relatively low mechanical strength, and therefore a value of 0.0429 was measured in Formula 1, which is lower than the value of Example 1.
[0198] Comparative Example 1 used the same biomass-derived raw materials as Example 3, but the presence of fine powder and low SiH4 deposition resulted in a larger internal pore structure in the final active material, thus the value in Equation 1 was relatively low. Comparative Example 2 did not undergo the final surface carbon coating process, and Comparative Example 3 showed a relatively low value in Equation 1 compared to Comparative Example 1, due to a significantly lower SiH4 deposition amount. Finally, in the case of Comparative Example 4, because the outermost carbon coating temperature was lower, the value in Equation 1 was also measured to be relatively low.
[0199] Furthermore, in Comparative Example 5, no carbon coating was formed as in Comparative Example 2, resulting in a decrease in hardness value. In Comparative Example 6, the outermost carbon coating time was extended, leading to an increase in the overall hardness value of the composite. Additionally, in Comparative Example 7 (corresponding to carbon-coated Mg-doped silicon oxide), the modulus and hardness values were found to exceed the ranges defined in this disclosure.
[0200] <Manufacturing the Negative Electrode>
[0201] A negative electrode slurry (solid content concentration of about 25% by weight) is prepared by adding a negative electrode active material containing silicon-based active materials as shown in Table 1, a negative electrode conductive material, and a binder made of polyacrylamide in a weight ratio of 80:10:10 to distilled water, which is used as a solvent for forming the negative electrode slurry.
[0202] In one embodiment, the negative electrode conductive material is carbon black (specific surface area: 45 m²). 2 / g, diameter: 30nm to 50nm).
[0203] As a mixing method, the negative electrode conductive material, binder and water are dispersed at 2,500 rpm for 30 minutes using a homogenizer, and then the silicon-based active material is added and dispersed at 2,500 rpm for 30 minutes to prepare the negative electrode slurry.
[0204] The negative electrode slurry was prepared at 85 mg / 25 cm⁻¹ 2 The loading amount was coated on both sides of a copper current collector (thickness: 8 μm) serving as the negative electrode current collector layer, rolled and dried in a vacuum oven at 130 °C for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as the negative electrode (thickness of the negative electrode: 41 μm, porosity of the negative electrode: 40.0%).
[0205] <Experimental Example>
[0206] A coin half-cell was fabricated using lithium metal as the negative electrode for a lithium secondary battery, and charge / discharge tests were conducted at a C rate of 0.1C. Charging was performed in CC / CV mode at 0.005C with a cutoff of 5mV, and discharging was performed in CC mode up to 1.0V. The results are shown in Table 2 below.
[0207] [Table 2]
[0208] As shown in Table 2, for the embodiments and comparative examples of this disclosure, the reduction rate of capacity and efficiency at electrode densities of 1 g / cc to 1.3 g / cc relative to those at electrode densities of 0.9 g / cc to 0.99 g / cc is recorded in Table 2, and it is confirmed that the comparative examples exhibit a greater reduction compared to the embodiments. For example, the embodiments exhibit high-capacity anodes (above 1,700 mAh / g) with a capacity reduction rate of about 1.2% and an initial efficiency reduction of about 1.0%, while the comparative examples show greater degradation of physical properties due to rolling.
[0209] In the numerical comparisons in Table 2, Comparative Examples 1, 6, and 7 showed relatively low initial efficiency reductions, but higher capacity reduction rates compared to the Examples. On the other hand, Comparative Examples 2 and 5 showed smaller capacity reduction rates, but relatively larger initial efficiency reductions. Similarly, Comparative Examples 3 and 4 showed similar results to Comparative Example 1.
[0210] For reference, Comparative Example 7 uses SiO, whose hardness and modulus values are outside the range defined in this disclosure, so its capacity is lower than that of the embodiments, making it unsuitable for the intended application.
[0211] In the embodiments of this disclosure, silicon-carbon composites satisfying the physical properties shown in Table 1 are used. By using resin-based porous carbon, the material exhibits relatively high mechanical strength and well-developed micropores. Therefore, the embodiments in Table 1 show high modulus values of approximately 15 GPa to 25 GPa, indicating excellent elastic properties before plastic deformation, less expansion during discharge, and more uniform formation of the irreversible phase with increasing sphericity, resulting in excellent efficiency characteristics.
[0212] On the other hand, the comparative examples used biomass-based materials, which have the characteristic of a higher proportion of mesopores and macropores inherent in biomass. As a result, the comparative examples exhibited inferior properties compared to the examples. Furthermore, since the total pore volume of each type of porous carbon is different, the amount of silicon that can be deposited is also different, resulting in a lower modulus of less than about 15 GPa, thus leading to inferior properties compared to the examples.
[0213] Furthermore, the hardness of the examples is also superior compared to the comparative examples. Hardness represents the resistance required to induce small local deformations on the material surface and indicates the surface's ability to withstand local indentation. This result indicates that, under the same indentation conditions, the material particles in the comparative examples exhibit more severe fracture than those in the examples.
[0214] In embodiments of this disclosure, at high voltage density, the above characteristics suggest that the electrodes exhibit fewer electrical short circuits, and due to these characteristics, the efficiency reduction in the embodiments is relatively small.
[0215] Although the technology of this disclosure has been described with reference to embodiments, those skilled in the art will understand that various modifications and changes can be made to the various embodiments of this disclosure without departing from the technical scope of the various embodiments of this disclosure as defined in the appended claims. Therefore, the technical scope of the various embodiments of this disclosure is not limited to the detailed description of the invention herein, but should be determined by the scope defined in the claims.
Claims
1. A negative electrode active material for lithium secondary batteries, the negative electrode active material for lithium secondary batteries comprising a silicon-carbon (Si / C) composite, the silicon-carbon composite having a modulus value (A) of 15 GPa to 25 GPa representing the stiffness of the material and a hardness value (B) of 2,500 MPa to 5,000 MPa representing the resistance of the material surface to scratches or indentations.
2. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the modulus value (A) and the hardness value (B) satisfy Equation 1: [Formula 1] 0.1≤B 3 / A 2 。 3. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the silicon-carbon composite comprises porous carbon and silicon deposited on the porous carbon. Furthermore, based on 100 parts by weight of the silicon-carbon composite, the silicon content is between 40 parts by weight and 60 parts by weight.
4. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the silicon-carbon composite has an average particle size (D50) of 1 μm or more to 10 μm or less.
5. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the negative electrode active material for lithium secondary batteries further comprises a carbon-based active material.
6. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the content of the silicon-carbon composite is less than 80 parts by weight based on 100 parts by weight of the negative electrode active material.
7. A method for manufacturing a negative electrode active material, the method comprising: Prepare porous carbon; and Silicon is deposited on the porous carbon to form a silicon-carbon composite. The silicon content is between 40 and 60 parts by weight, based on 100 parts by weight of the silicon-carbon composite. Furthermore, the silicon-carbon composite has a modulus value (A) of 15 GPa to 25 GPa and a hardness value (B) of 2,500 MPa to 5,000 MPa.
8. The method according to claim 7, wherein the porous carbon is prepared from a resin-based porous carbon raw material.
9. The method according to claim 7, wherein the porous carbon has a first pore diameter of less than 2 nm in a proportion of more than 90% when measured by nitrogen adsorption, and The porous carbon has a second pore with a diameter of 2 nm to 50 nm or less when measured by the nitrogen adsorption method, and the ratio of such pores is less than 10%.
10. A negative electrode composition for a lithium secondary battery, the negative electrode composition comprising a negative electrode active material, a negative electrode conductive material, and a negative electrode binder according to any one of claims 1 to 6.
11. The negative electrode composition for lithium secondary batteries according to claim 10, wherein the content of the negative electrode active material is 40 parts by weight or more based on 100 parts by weight of the negative electrode composition.
12. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: Negative current collector layer; and A layer of negative electrode active material disposed on one or both surfaces of the negative electrode current collector layer. The negative electrode active material layer comprises the negative electrode composition or its cured form according to claim 10.
13. The negative electrode for a lithium secondary battery according to claim 12, wherein the negative electrode current collector layer has a thickness of 1 μm or more to 100 μm or less, and The negative electrode active material layer has a thickness of more than 5 μm and less than 500 μm.
14. A lithium secondary battery, the lithium secondary battery comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 12; A membrane disposed between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Medical systems, devices and related methods
KR1020240144998A
Feed for eel fry, method for producing eels, and inhibitor of morphological abnormalities in eel fry
KR1020250151521A
